EXPRESSION OF PARALINGUISTIC MEANS IN THE SPEECH ETIQUETTE OF DIFFERENT LINGUOCULTURES - Durdona Abduazizova Abdazukhurovna (Western European Studies, 2025)
The article examines verbal and paralinguistic etiquette within the national and cultural frameworks of Uzbek, English, and Russian linguocultures. Special attention is given to the role of paralinguistic means—such as gestures, facial expressions, intonation, voice timbre, and body posture—in communication and in shaping cultural norms of interaction. The author distinguishes between two types of etiquette: internal national-cultural etiquette, based on traditional norms and practices of a specific culture, and international etiquette, which regulates intercultural communication and requires consideration of the cultural characteristics of all participants. The study emphasizes the importance of international paralinguistic etiquette in business communication, where gestures, intonation, posture, interpersonal distance, and emotional restraint are strictly regulated. The findings demonstrate that verbal and paralinguistic etiquette form a unified system of culturally determined communicative behavior grounded in principles of politeness, respect, self-restraint, and positive interpersonal orientation.
Keywords: verbal and paralinguistic etiquette; national and cultural specificity